Management of antiplatelet therapy inpatients at risk for coronary StentThrombosis undergoing non-cardiac surgery - Motovska, Zuzana (Drugs, 2011)
Percutaneous coronary interventions (PCIs) have become the most commonly performed coronary revascularization procedures. At the same time, there is an increased likelihood that patients with intracoronary stents will need to undergo surgery. Two serious consequences emerge from this situation: (i) stent thrombosis in relation to discontinuation of antiplatelet therapy, and (ii) major bleeding in relation to continuation of antiplatelet therapy. The best solution to overcome the risks resulting from surgery performed in patients after stent implantation is to postpone the operation until after re-endothelialization of the vessel surface is completed. Expert recommendations advise that patients can be sent for non-cardiac surgery 3 months after bare-metal stent PCI and 12 months after drug-eluting stent PCI, with continuation of aspirin therapy. Difficult decisions regarding antiplatelet management arise when a patient that is still receiving dual antiplatelet therapy with aspirin and a thienopyridine has to undergo surgery that cannot be postponed. Discussions between the treating cardiologist, the surgeon and the anaesthesiologist about this situation are recommended in order to achieve a reasonable expert consensus.
Keywords: inhibitory agregace trombocytů; cévní protézy; Inpatients; chirurgie operační; Coronary Thrombosis; Risk Factors; Aspirin; kombinovaná farmakoterapie; koronární trombóza; Surgical Procedures, Operative; Stents; Drug Therapy, Combination; Time Factors; Blood Vessel Prosthesis; hospitalizovaní pacienti; lidé; Humans; pyridiny; rizikové faktory; stenty; časové faktory; Pyridines; Platelet Aggregation Inhibitors